2006
DOI: 10.1051/0004-6361:200500219
|View full text |Cite
|
Sign up to set email alerts
|

The methane ice rich surface of large TNO 2005 FY9: a Pluto-twin in the trans-neptunian belt?

Abstract: Context. The population of known large trans-neptunian objects (TNOs) is growing very fast and the knowledge of their physical properties is a key issue to understand the origin and evolution of the Solar System. Aims. In this paper we studied the surface composition of the recently discovered TNO 2005 FY 9 , one of the largest known TNOs (∼0.7 times the diameter of Pluto, i.e. 1600 km, if the albedo is similar, or 3100-1550 km in diameter assuming an albedo range 0.2 < p V < 0.8).Methods. We report visible an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
115
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(136 citation statements)
references
References 29 publications
19
115
0
1
Order By: Relevance
“…This "matrix shift" occurs when the molecules are dissolved in frozen N 2 and was first seen in the CH 4 spectrum of Triton (Cruikshank et al 1993;Quirico et al 1999) based on laboratory studies by Quirico & Schmitt (1997). CH 4 band shifts to lower frequencies have also been observed in the spectrum of Pluto (Douté et al 1999), Quaoar (Licandro et al 2006a), and Makemake (Licandro et al 2006b). The coexistence of NH 3 and N 2 ices of solar system objects such as Enceladus or Charon is also thought to be very likely (Dalton 2010;Dalton et al 2010).…”
Section: Introductionmentioning
confidence: 83%
“…This "matrix shift" occurs when the molecules are dissolved in frozen N 2 and was first seen in the CH 4 spectrum of Triton (Cruikshank et al 1993;Quirico et al 1999) based on laboratory studies by Quirico & Schmitt (1997). CH 4 band shifts to lower frequencies have also been observed in the spectrum of Pluto (Douté et al 1999), Quaoar (Licandro et al 2006a), and Makemake (Licandro et al 2006b). The coexistence of NH 3 and N 2 ices of solar system objects such as Enceladus or Charon is also thought to be very likely (Dalton 2010;Dalton et al 2010).…”
Section: Introductionmentioning
confidence: 83%
“…1 in two spectra of Triton recorded on 1995 (the band on the righthand side in the triplet around 1.86 µm) and 1998 (the first visible band starting from 1.87 µm). The same unidentified band could be present, like a weak shoulder of the more prominent CH 4 feature, in Makemake's low-resolution spectra shown by Brown et al (2007) and Licandro et al (2006a).…”
Section: Discussionmentioning
confidence: 80%
“…The first one is constituted by TNOs whose spectra are dominated by methane-ice absorption bands, such as Pluto Protopapa et al 2008), Eris (Brown et al 2005;Licandro et al 2006b;Dumas et al 2007), and Makemake (Licandro et al 2006a;Brown et al 2007;Tegler et al 2007;Tegler et al 2008). A similar spectrum is also shown by Triton (Cruikshank et al , 2000Quirico et al 1999), probably an originally isolated TNO that was then captured by Neptune (McKinnon et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The average albedo is estimated to be p v = 0.71 +0.08 −0.02 (Ortiz et al 2012), which is in agreement with the estimation from the thermal data (Lim et al 2010). Spectroscopic observations of Makemake have revealed strong absorption bands associated with methane (Barkume et al 2005;Licandro et al 2006;Brown et al 2007;Tegler et al 2007Tegler et al , 2008. Brown et al (2007) reported the presence of ethane features and no apparent evidence for N 2 and CO. Tegler et al (2007Tegler et al ( , 2008 reported a small shift of the CH 4 bands in their spectra of Makemake in comparison with a model fit, suggesting the presence of trace amounts of N 2 ice.…”
Section: (136472) Makemakementioning
confidence: 99%